Multimodal storytelling in the news: Sequenced images as ideological scripts of othering. (April 2019) - Chovanec, Jan
Highlights: Sequenced documentary news photographs can be used for ideologically-laden storytelling. There are diverse inter-semiotic relations between the visual and the verbal tracks (photographs and captions). Visual storytelling can complement or even contradict the news story, which has a different structure. Sequenced visual narratives can contain implicit stereotypical scripts of othering. Abstract: The paper examines the process of visual othering in documentary photographs in print news stories. Adopting the perspective of multimodal critical discourse analysis, it demonstrates how a series of images can construct, in combination with the textual component in image captions, a coherent and self-contained narrative reflecting a shared stereotypical script. The articles argues that the traditional exploration of text-image relations in the press should be extended by considering the storytelling potential of sequenced images in view of the fact that such images can manifest subtle patterns of multimodal manipulation. The implications of this study are relevant for our understanding of the semiotic potential of sequenced images in news stories, as distinct from the genre of print or online picture galleries, and of how such storytelling contributes towards articulating discourses of prejudice.